PROSES PEMBUATAN BODY CALIPER PADA MOTOR MATIC DI PT. XXX - Muhammad Yusuf Nurfani (Jurnal Ilmiah Teknik, 2024)
The body caliper is a crucial component of the braking system designed to ensure safety and security while driving, especially on two-wheeled vehicles. For the production of the body caliper on the , Aluminium Alloy AA 319 T6 is used due to its high strength and lightweight properties, consisting of 90.48% Aluminum, 2.7% Chromium, 6.6% Silicon, and 0.22±0.02% Magnesium. The manufacturing process involves melting the metal and pouring it into molds. Electromagnetic penetration is used to detect conductive structures and cracks in the raw material. Hardening tests are conducted using optical microscopy, scanning electron microscopy (SEM), energy dispersive X-ray (EDX), and X-ray diffraction (XRD), as well as hardness measurement and tensile testing. The results show an improvement in the mechanical properties of the AA319 alloy after T6 heat treatment, with a hardness of 124.2 ± 3.2 HV, tensile strength of 298 ± 3.0 MPa, yield strength of 201 ± 2.6 MPa, and elongation to fracture of 4.5 ± 0.3%.